1989
DOI: 10.1590/s0074-02761989000400016
|View full text |Cite
|
Sign up to set email alerts
|

El rol de Cyrtograpsus angulatus (Crustacea; Brachyura) en los ciclos de vida de Microphallus szidati (Digenea; Microphallidae) y Falsifilicollis chasmagnathi (Acanthocephala; Filicollidae): algunos aspectos de su ecologia parasitaria

Abstract: Based on a study of the larvae from two helminth species parasitizing the crab Cyrtograpsus angulatus Dana, 1851 (Microphallus szidati Martorelli, 1986 and Falsifilicollis chasmagnathi Holcman-Spector et al., 1977), from Mar chiquita lagoom (Argentina) together with the analyses of their life cycles and rates of prevalence, intensity and association coefficient (compared in definitive and intermediate host) the following conclusions have been reached: a) C. angulatus suns to be an excellent intermediate host i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…-The body measurements and the presence of a genital atrium containing 10 atrial pockets agree with metacercariae of L. cruzi. The metacercariae developed eggs in saline solution at 37 • C. With the exception of a smaller ovary (37-54 by 56-68 vs. 52-60 by 90-100) observed in L. cruzi from our study, all other measurements agree with those reported by Martorelli (1988) who first reported L. cruzi parasitizing the gonads, muscle, and connective tissue of the freshwater shrimp Palaemonetes argentinus Nobili, 1901. This shrimp is one of the most widely distributed decapods in Argentina, occurring both in fresh water and brackish water areas (Spivak, 1997).…”
Section: Levinseniella Cruzi Travassos 1920supporting
confidence: 90%
See 3 more Smart Citations
“…-The body measurements and the presence of a genital atrium containing 10 atrial pockets agree with metacercariae of L. cruzi. The metacercariae developed eggs in saline solution at 37 • C. With the exception of a smaller ovary (37-54 by 56-68 vs. 52-60 by 90-100) observed in L. cruzi from our study, all other measurements agree with those reported by Martorelli (1988) who first reported L. cruzi parasitizing the gonads, muscle, and connective tissue of the freshwater shrimp Palaemonetes argentinus Nobili, 1901. This shrimp is one of the most widely distributed decapods in Argentina, occurring both in fresh water and brackish water areas (Spivak, 1997).…”
Section: Levinseniella Cruzi Travassos 1920supporting
confidence: 90%
“…This species was described by Holcman-Spector et al (1977) in N. granulata from the Santa Lucía estuary in Uruguay. Profilicollis chasmagnathi was also reported in C. angulatus from Mar Chiquita coastal lagoon (Martorelli, 1989), and in C. angulatus and N. granulata from the Bahía Blanca estuary (La Sala & Martorelli, 2007). Remarks.…”
Section: Family Acuariidae Subfamily Acuariinaementioning
confidence: 88%
See 2 more Smart Citations
“…In South America, researches about physiological and behavioral alterations in crustaceans acting as intermediate hosts of acanthocephalans are scarce and have been done only with estuarine and sea crabs (Martorelli, 1989;Haye and Ojeda, 1998;Rojas and Ojeda, 2005).…”
Section: Introductionmentioning
confidence: 99%